Barrier, mechanical, and thermal properties of the three-layered co-extruded blown polyethylene/ethylene–vinyl alcohol/low density polyethylene film without tie layers. (June 2017) - Ge, Changfeng; Lei, Kai; Aldi, Robert
This article investigates three-layer co-extruded blown film comprised of low-density polyethylene (LDPE)/ethylene–vinyl alcohol (EVOH)/LDPE without adhesion layers. Various thicknesses of pure EVOH were sandwiched by outer LDPE layers blended with linear low-density polyethylene-grafted-maleic anhydride (LLDPE- g -MAH) as compatibilizer in concentrations from 0 wt% to 2.0 wt%. The study found that a mere 3-μ EVOH layer can achieve a 180 times improvement of oxygen barrier properties as compared to the control sample. When the EVOH loading is 10–15 wt% of the total film mass, the addition of LLDPE- g -MAH into the outer layers indicated a positive synergistic effect by enhancing barrier properties. In contrast, when the EVOH loadings are at 5 wt% and 7.5 wt%, the barrier properties of the film was reduced. Layer-to-layer interaction between the LDPE and EVOH was notably improved as demonstrated by a 26–42% increase of interlaminate peel strength in the presence of 0.5–2 wt% LLDPE- g -MAH in all samples. Congruently, the introduction of the LLDPE- g -MAH into the outer LDPE layers also resulted in an increased dart impact toughness and tensile strength for the film. The EVOH crystallinity showed a reduction after adding LLDPE- g -MAH, particularly apparent for the lower EVOH concentrations.